ANALISIS LAYANAN KEAMANAN SISTEM KARTU TRANSAKSI ELEKTRONIK MENGGUNAKAN METODE PENETRATION TESTING - Azis, Huzain; Fattah, Farniawati (Teknik Informatika Fakultas Ilmu Komputer Univeristas Muslim Indonesia, 2019)
Payment transactions developed along with technological developments, now days technology supports digital payment, each type of digital transaction has its own security services, this study focus on the analysis of security services (confidentiality, integrity and availability) using the Penetration Testing method on magnetic stripe cards as a payment transaction playground facility, then comparing security services to the Radio Frequency Identification (RFID) electronic transaction tool. The results of this study are RFID electronic transaction cards that provide a more complete security service as an electronic payment transaction.